Pycnogonids (Arthropoda: Pycnogonida) from French Cruises to Melanesia - Bamber, Roger N. (Zootaxa, 2004)
Seventy specimens of pycnogonid from New Caledonia and the Solomon Islands, collected during cruises from the Paris Museum, are described. No pycnogonids have been recorded previously from the Solomon Islands. Of the sixteen species identified, three ammotheids, Bathyzetes umbrella, Cilunculus cymobostrychos and C. mergus, are new to science. The distinctions of the sibling species Colossendeis pipetta Stock, 1991 and C. sinuosa Stock, 1997 are analyzed morphometrically. The pycnogonid fauna of the Melanesia-Micronesia-Polynesia region is summarized.